Managing change in academic library - Prokopčik, Marija (Knjižnica, 2013)
Purpose: The main objective of this article is to ascertain some most significant fields of the academic library activities, which have (or could have) an impact on strengthening the library's role as a partner in academic community, as well as to perform assessment of Vilnius University Library (thereinafter VUL) capacities in order to see what kind of current or future activities performed by the library may contribute to the building-up of such role in Vilnius University (thereinafter VU) community. Methodology/approach: Analysis of LIS professional literature of the latter five years reveals the key trends in development of academic libraries, their innovative change and challenges - partnerships of open access, managing of research data; research support; research assessment, Library scientific research, as well as allows to perform situation analysis of one particular library in order to see if and at what scale these identified trends can be traced in VUL. Results: It was established that VUL contributes to the idea and practical implementation of open access, collaborates with VU and Lithuania's academic community in the projects of research data management, takes an active part in carrying out bibliometric research, helps to form a range of research support services, promotes the Library's scholarly research and contributes to formation of the institution's research potential. Research limitation: This article focuses on analysis of one academic library (VUL) and its activities. Such issues like studies support, library as a space for communication, professional assistance in research events organization, improvement of information and media literacy were deliberately not covered. Originality/practical implications: Identification of common trends and measures of their practical implementation in one particular institution may be useful for other libraries planning the strategy of change and (or) implementing selected solutions.
Keywords: visokošolske knjižnice; odprt dostop; podpora raziskovanju; upravljanje podatkov; ocenjevanje raziskovalnega dela; upravljanje sprememb